Uniform Strain-Dependent Thermal Conductivity of Pentagonal and Hexagonal Silicene - Liu, Huake; Qin, Guangzhao; Hu, Ming (Frontiers in Materials, 2021)
Two-dimensional (2D) pentagonal monolayer structures have shown promising characteristics and fascinating physical and chemical properties. The disparate strain dependent thermal conductivity of two dimensional penta-structures was reported but the difference between the silicon based pentagonal and hexagonal structures is barely investigated. In this work, based on first-principles calculations, we studied the strain modulated phonon transport behavior of two 2D pentagonal (penta-SiH and bilayer penta-Si) and one hexagonal silicene structures (H-silicene), of which the penta-SiH and H-silicene mean the structures are hydrogenated for the purpose of thermodynamical stability. We find that the silicon based pentagonal structure also presented a different strain dependent thermal conductivity from other pentagonal materials, such as penta-graphene, penta-SiC or penta-SiN. Moreover, even with the similar strain dependent thermal transport behavior in penta-SiH and bilayer penta-Silicene, we find that the governing mechanism is still different. For both pentagonal silicene structures, the thermal conductivity presents a large improvement at first as tensile strain increases from 0 to 10% and then stabilizes with strain larger than 10%. Detailed analysis shows that, the in-plane modes contributed the most part to the group velocity enhancement under strains in penta-SiH which is opposite from the bilayer penta-silicene, although the phonon group velocity and phonon lifetime of both structures increase with applied strain. On the other hand, similarity was found in pentagonal silicene and hexagonal silicene despite the differences in geometry structures. Furthermore, based on the detailed analysis between the pentagonal (penta-SiH) and hexagonal silicene structures (H-silicene), the difference in out-of-plane phonon scattering can not be ignored: different major scattering channels of the out-of-plane flexual modes result in different thermal conductivity sensitivity to strains and the disparity in anharmonicity leads to the different thermal conductivity under no strain.